Identifikasi Risiko Terhadap Kinerja Waktu Pada Proyek Pembangunan Passenger Terminal Building Bandara Internasional Dhoho Kediri - Kirana, Nabilah Chandra (Jurnal Vokasi Teknik Sipil, 2023)
Construction projects are inseparable from the element of risk. Risks which are uncertain events can cause disruption in project performance, one of which is project time performance. Project time performance is one of the benchmarks in project success. At this time there is one fairly complex project that is being implemented, namely the Dhoho Kediri International Airport Passenger Terminal Building construction project. This study aims to identify risk factors related to project time performance in order to avoid delays in project completion. The method used in this research is a qualitative method in the form of a literature study. The data collection technique used is a literature study of several journals or previous research articles that have discussed construction project risk management, especially on project time performance. From the results obtained, there are 38 risk identifications which are divided into 5 categories including 10 risk identification material categories, 8 risk identification environmental categories, 11 risk identification management categories, 4 risk identification design categories and 5 risk identification equipment categories.